Adenosine A2a receptors form distinct oligomers in protein detergent complexes. Issue 18 (2nd September 2016) - Schonenbach, Nicole S.; Rieth, Monica D.; Han, Songi; O'Malley, Michelle A.
Abstract : The human adenosine A2a receptor (A2aR) tunes its function by forming homo‐oligomers and hetero‐oligomers with other G protein‐coupled receptors, but the biophysical characterization of these oligomeric species is limited. Here, we show that upon reconstitution into an optimized mixed micelle system, and purification via an antagonist affinity column, full‐length A2aR exists as a distribution of oligomers. We isolated the dimer population from the other oligomers via size exclusion chromatography and showed that it is stable upon dilution, thus supporting the hypotheses that the A2aR dimer has a defined structure and function. This study presents a crucial enabling step to a detailed biophysical characterization of A2aR homodimers. Abstract : Full‐length adenosine A2a receptor forms multiple oligomers in vitro . Oligomer species can be separated by size exclusion chromatography. Separated A2aR dimers are stable and do not redistribute into mixed populations.